2021
DOI: 10.5114/pjp.2021.106446
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial adenocarcinoma with gastrointestinal differentiation – a newly described entity, with morphologic diversity

Abstract: Gastrointestinal type of endometrial carcinoma is a newly described entity for which clearly defined diagnostic criteria have only recently been published. Among morphologic criteria, gastrointestinal mucinous adenocarcinoma of endometrium must not show a typical endometrioid component. We present a case with morphologic diversity, with areas showing gastric and intestinal differentiation as well as an endometrioid-like component. However, the endometrioid-like component not only did not show classic squamous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…Mucinous carcinoma of the gastrointestinal type (MCG) is an emerging subtype of mucinous carcinoma that may be of distinct clinicopathologic significance. 18,26,[92][93][94][95][96][97][98][99][100] The entity encompasses tumors with gastric-type morphology, intestinal-type morphology, or both. Although diagnostic criteria for MCG remain unclear, the entity was recognized in the 5th edition of the WHO Classification.…”
Section: Mucinous Carcinomas Of the Gastrointestinal Typementioning
confidence: 99%
See 3 more Smart Citations
“…Mucinous carcinoma of the gastrointestinal type (MCG) is an emerging subtype of mucinous carcinoma that may be of distinct clinicopathologic significance. 18,26,[92][93][94][95][96][97][98][99][100] The entity encompasses tumors with gastric-type morphology, intestinal-type morphology, or both. Although diagnostic criteria for MCG remain unclear, the entity was recognized in the 5th edition of the WHO Classification.…”
Section: Mucinous Carcinomas Of the Gastrointestinal Typementioning
confidence: 99%
“…The cases reported by Abiko et al, 99 Hino et al, 100 appeared to be pure gastric-type adenocarcinomas whereas the cases reported by McCarthy et al 103 were endometrioid carcinomas with focal areas of gastric-type epithelium. Travaglino et al 97 and Stolnicu et al 98 both emphasized the potential for morphologic heterogeneity, including poorly differentiated areas with discohesive cells, high nuclear grade, signet ring cell features and a variety of other morphologic attributes that may mimic MCU, endometrioid, clear cell, and serous carcinoma. Tumors with intestinal type morphology display varying numbers of goblet cells in a background of columnar or cuboidal cells with mucinous or eosinophilic cytoplasm.…”
Section: Mucinous Carcinomas Of the Gastrointestinal Typementioning
confidence: 99%
See 2 more Smart Citations